Publier la poésie action ? - Gaëlle Théval (Itinéraires)
Bernard Heidsieck's action poetry brings the poem out of the book and into performance. Nevertheless, it also manifests in publications, whether exclusively on discs and cassettes, or exclusively in magazines, or in books. Many of these publications adopt the hybrid form of the audio-book. If the poem finds its culmination in performance, what status should be given to its other physical/material manifestations? The heterogeneity of the medium has contributed to blurring the contours of the work, and to favouring an often partial approach to it. However, the publication of a sound poem on CD does not necessarily make the audio-book object a closed whole: what is published in the audio-book is not the work itself, but a set of materials activated during the performances. A second question then arises: how is the work considered because of these modes of publication? The poem is part of a transmedia circulation in its different modes of implementation. Its various editions give the work alternative modes of expression, pointing to the fundamental and intrinsic “aesthetic [inter- and] trans-mediality” (Vouilloux, 2015, p. 64), confirming a form of mediological inassignation.